Bridging dimensions: a comparative analysis of 2D and 3D in vitro models for hepatocellular carcinoma research - Valente, Leticia Cardoso [UNESP]; Riechelman-Casarin, Luana [UNESP]; Esteves, Laura Latrechia Pacheco; Bacil, Gabriel Prata [UNESP]; da Silva, Tereza Cristina; Vinken, Mathieu; Cogliati, Bruno; Friedman, Scott L.; Columbano, Amedeo; Barbisan, Luís Fernando [UNESP]; Romualdo, Guilherme Ribeiro [UNESP] (Springer Nature, 2025)
The tumor microenvironment (TME) influences hepatocellular carcinoma (HCC) behavior and disease progression. Cell–cell dynamics of non-parenchymal components, such as hepatic stellate cells (HSC), are key factors in understanding HCC onset and progression. This study established mono- and co-culture in vitro HCC models in both 2D and 3D configurations to investigate HCC cell behavior at both functional and transcriptional levels. Human HCC C3A cells were co-cultured with human HSC LX2 cells or alone in ultra-low attachment plates to form spheroids (3D) or in a transwell system (2D). In the 2D model, the paracrine signaling of HSC-HCC cells promoted colony formation and HCC cells motility compared to the C3A monolayer, showing a pro-inflammatory transcriptomic signature through a positive regulation of canonical NF-κB pathway. In the 3D model, co-culture spheroids exhibited higher cell viability, enhanced angiogenesis, migration, and extracellular matrix (ECM)-related transcriptomic hallmarks compared to C3A monoculture. Regardless of the configuration, co-culture models shared 74 genes, including angiogenesis, proteolysis and response to wounding functional annotations, indicating a LX2-induced pro-tumoral signature in C3A cells. The 2D vs. 3D comparison revealed that the 3D model enriched proliferation-related genes in monocultured C3A spheroids compared to C3A monolayers, whilst co-culture spheroids showed cholesterol, angiogenesis, migration and ECM annotations compared to co-culture transwell model. These findings reinforce the importance of HSC as key microenvironmental cellular components in HCC and highlight how cellular dynamics modify HCC cell behavior in vitro.